MIRA-SNuPE, a quantitative, multiplex method for measuring allele-specific DNA methylation - Lee, Dong-Hoon (Landes Bioscience, 2011)
5-methyl-C (5mC) and 5-hydroxymethyl-C (5hmC) are epigenetic marks with well-known and putative roles in gene regulation, respectively. These two DNA covalent modifications cannot be distinguished by bisulfite sequencing or restriction digestion, the standard methods of 5mC detection. The methylated CpG island recovery assay (MIRA), however, specifically detects 5mC but not 5hmC. We further developed MIRA for the analysis of allele-specific CpG methylation at differentially methylated regions (DMRs) of imprinted genes. MIRA specifically distinguished between the parental alleles by capturing the paternally methylated H19/Igf2 DMR and maternally methylated KvDMR1 in mouse embryo fibroblasts (MEFs) carrying paternal and maternal duplication of mouse distal Chr7, respectively. MIRA in combination with multiplex single nucleotide primer extension (SNuPE) assays specifically captured the methylated parental allele from normal cells at a set of maternally and paternally methylated DMRs. The assay correctly recognized aberrant biallelic methylation in a case of loss of imprinting. The MIRA-SNuPE assays revealed that placenta exhibited less DNA methylation bias at DMRs compared to yolk sac, amnion, brain, heart, kidney, liver and muscle. This method should be useful for the analysis of allele-specific methylation events related to genomic imprinting, X chromosome inactivation and for verifying and screening haplotype-associated methylation differences in the human population.